DOCKING STUDIES OF CURCUMIN AS A POTENTIAL LEAD COMPOUND TO DEVELOP NOVEL DIPEPTYDYL PEPTIDASE-4 INHIBITORS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Interaction of curcumin to dipeptydyl peptidase-4 (DPP-4) has been studied by employing docking method using Molecular Operating Environment (MOE) and AutoDock as the docking software applications. Although MOE can sample more conformational spaces that represent the original interaction poses than AutoDock, both softwares serve as valid and acceptable docking applications to study the interactions of small compound to DPP-4. The calculatedfree energy of binding (AGblndlnsJ results from MOEand AutoDockshows that curcuminis neededto be optimizedto reachsimilaror betterAGbind/ng compareto the referencecompound.Curcumincan be consideredas a good lead compound in the development of new DPP-4 inhibitor. The results of these studies can serve as an initial effort of the further study.